The utility of preemptive mass influenza vaccination in controlling a SARS outbreak during flu season - Qingling Zeng; Kamran Khan; Jianhong Wu; Huaiping Zhu (Mathematical Biosciences and Engineering)
During flu season, respiratory infections can cause non-specificinfluenza-like-illnesses (ILIs) in up to one-half of the general population. If afuture SARS outbreak were to coincide with flu season, it would become exceptionallydifficult to distinguish SARS rapidly and accurately from other ILIs, given thenon-specific clinical presentation of SARS and the current lack of a widely available,rapid, diagnostic test. We construct a deterministic compartmental model to examine thepotential impact of preemptive mass influenza vaccination on SARS containment during ahypothetical SARS outbreak coinciding with a peak flu season. Our model was developedbased upon the events of the 2003 SARS outbreak in Toronto, Canada. The relationship ofdifferent vaccination rates for influenza and the corresponding required quarantinerates for individuals who are exposed to SARS was analyzed and simulated under differentassumptions. The study revealed that a campaign of mass influenza vaccination prior tothe onset of flu season could aid the containment of a future SARS outbreak bydecreasing the total number of persons with ILIs presenting to the health-care system,and consequently decreasing nosocomial transmission of SARS in persons underinvestigation for the disease.